Short Communication. Effect of saline soil parameters on endomycorrhizal colonisation of dominant halophytes in four Hungarian sites - Füzy, A.; Biró, B.; Tóth, T. (Spanish Journal of Agricultural Research, 2010)
Soil and root samples were collected from the rhizosphere of dominant halophytes (Artemisia santonicum, Aster tripolium, Festuca pseudovina, Lepidium crassifolium, Plantago maritima and Puccinellia limosa) at four locations with saline soils in Hungary. The correlations- between arbuscular mycorrhiza (AM) fungal colonisation parameters (% colonisation, % arbuscules) and soil physical, chemical and biological parameters were determined Endomycorrhiza colonisation was found to be negatively correlated with the electric conductivity of the soil paste, the salt-specific ion concentrations and the cation exchange capacity, showing the sensitivity of AM fungi at increasing salt concentrations, independently of the types of salt-specific anions. A positive correlation was detected between the mycorrhiza colonisation and the abundance of oligotroph bacteria known to be the less variable and more stable (k-strategist) group. This fact and the negative correlation found with the humus content underlines the importance of nutrient availability and the limitations of the symbiotic interactions in stressed saline or sodic soils.